A Zinc Metalloprotease nas-33 Is Required for Molting and Survival in Parasitic Nematode Haemonchus contortus - Huang, Yan; Wu, Jie; Chen, Xueqiu; Tong, Danni; Zhou, Jingru; Wu, Fei; Zhang, Hui; Yang, Yi; Ma, Guangxu; Du, Aifang (Frontiers in Cell and Developmental Biology, 2021)
Molting is of great importance for the survival and development of nematodes. Nematode astacins (NAS), a large family of zinc metalloproteases, have been proposed as novel anthelmintic targets due to their multiple roles in biological processes of roundworms. In this study, we report a well conserved nas-33 gene in nematodes of clade V and elucidate how this gene is involved in the molting process of the free-living nematode Caenorhabditis elegans and the parasitic nematode Haemonchus contortus. A predominant transcription of nas-33 is detected in the larval stages of these worms, particularly in the apolysis phase of molting. Knockdown of this gene results in marked molecular changes of genes involved in cuticle synthesis and ecdysis, compromised shedding of the old cuticle, and reduced worm viability. The crucial role of NAS-33 in molting is closely associated with a G protein beta subunit (GPB-1). Suppression of both nas-33 and gpb-1 blocks shedding of the old cuticle, compromises the connection between the cuticle and hypodermis, and leads to an increased number of sick and dead worms, indicating essentiality of this module in nematode development and survival. These findings reveal the functional role of nas-33 in nematode molting process and identify astacins as novel anthelmintic targets for parasitic nematodes of socioeconomic significance.